Impacto da piscicultura em tanques-rede sobre a estrutura da comunidade zooplanctônica em um reservatório subtropical, Brasil. - Dias, Juliana Déo (Universidade Estadual de Maringá. Departamento de Biologia. Programa de Pós-Graduação em Ecologia de Ambientes Aquáticos Continentais., 2008)
This study evaluated the zooplankton structure near to net cages culture in Rosana Reservoir (Paranapanema River, PR/SP). The hypothesis was that the zooplankton abundance is greater near the net cages, due to the changes on physical and chemical conditions variables and to the increase of food resource availability, especially over time. In general, the alteration of rotifer, cladoceran and copepods species composition was high near to the net cages and downstream, and the highest zooplankton abundance were verified upstream of them. The zooplankton abundance varied according to pH, turbidity and water temperature, dissolved oxygen, nitrogen and phosphorus concentrations, beyond the food availability (heterotrophic flagellates) and this influence was registered, especially, along time. The predicted hypothesis was refuted, since the spatial variation of zooplankton abundance was different from expected, although the factors that influenced this variation during the experiment have been regarded as important for the community structure (physical and chemical variables and food resource availability). Only spatial and temporal variation of rotifer abundance corroborated the predicted hypothesis. Esse estudo avaliou a estruturação da comunidade zooplanctônica em uma área de instalação de tanques-rede no reservatório de Rosana, rio Paranapanema (PR/SP). A hipótese testada foi que a abundância do zooplâncton é maior no local onde foram instalados os tanques-rede, visto que essa atividade contribui para a alteração das condições físicas e químicas da água e o incremento da disponibilidade de alimento, principalmente ao longo do tempo. A composição de espécies de rotíferos, cladóceros e copépodes apresentaram, em geral, maior alteração próxima aos tanques-rede e a jusante dos mesmos e, maior abundância da comunidade, a montante dos tanques. O número de organismos variou em função do pH, turbidez e temperatura da água, oxigênio, nitrogênio e fósforo dissolvidos, além da disponibilidade de alimento (flagelados ...